Structural, elastic, electronic, optical and thermal properties of c-SiGe2N4 - Bouhemadou, A.; Yarub K.A, Al-Douri; Khenata, R.; Haddadi, K. (Springer Verlag, 2010)
Link to publisher's homepage at http://www.springerlink.com/